Pengaruh Konseling Terhadap Pemilihan Metode Kontrasepsi Jangka Panjang Pada Masa Nifas Di Sulawesi Selatan - Nur Laela; St. Nurbaya Panyura; Resmawati; Roni (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Background: Family planning is an effort made by humans to intentionally arrange marriage in the family not against the laws and morals of Pancasila for the welfare of the family. Through the family planning program, control will occur, namely controlling population growth so that it can improve the health and welfare of the family. Quality family planning services are not only related to services in the marketing of contraceptives, but also related to the provision of Interpersonal/Counseling communication to acceptors. Objective: To determine the effectiveness of aerobic dance and pregnancy exercise on the anxiety of pregnant women in the third trimester at Puskesmas Solo, South Sulawesi. Research Methods: This study uses quantitative methods, the type of research this research is a quasi-experimental (quasi-experimental) with a non-equevalent control group design. The population in this study was the population in this study were all postpartum mothers in the working area of ​​the Solo Public Health Center. The sampling technique in this study used a quota sampling technique. Results: Based on the statistical test analysis, the t-test price t-count is 3.151 so that 3.151>1.686 (t-count > t-table), thus H0 is rejected, Ha is accepted, meaning that the use of ABPK is more effective than leaflets on the selection of MKJP in the work area of ​​the Solo Health Center in 2021. Conclusion: The use of ABPK for the selection of post-partum contraceptives is more effective than the use of leaflet counseling. The results of this study can be a recommendation in the use of ABPK in an effort to increase the selection of contraception according to the needs of prospective acceptors. This research can be developed using a control group.